A Study on the Correlation between C-Reactive Protein Concentration and Teeth with a ≥5 mm Periodontal Pocket in Chronic Periodontitis Patients - Hee-Yung Chang; A-Reum Kim; Sung-Hee Pi; Hyung-Keun You (Hindawi Limited, 2020)
Objective. To evaluate the relationship between CRP levels and teeth with ≥5 mm PD in chronic periodontitis patients. Materials and Methods. We evaluated 49 patients with chronic periodontitis who visited the Department of Periodontology at Wonkwang University Dental Hospital. At the first visit, high-sensitive CRP testing of venous blood samples was performed, and correlations were statistically evaluated. Results. The mean hs-CRP level of patients diagnosed with severe periodontitis was 2.0 mg/L (0.13-13.95 mg/L). Statistically, patients with a high rate of teeth diagnosed with severe periodontitis are more likely to have higher hs-CRP level. Conclusion. Within the limits of this study, the number and proportion of teeth showing ≥5 mm PD was positively correlated with CRP concentration.